Anti-herpetic and anti-inflammatory activities of two new synthetic 22,23-dihydroxylated stigmastane derivatives - Michelini, Flavia Mariana (2008)
Stromal keratitis resulting from ocular infection with Herpes simplex virus type 1 (HSV-1) is a common cause of blindness. This report investigates the antiviral and anti-inflammatory properties of two new synthetic stigmastane analogs in the experimental model of HSV-1-induced ocular disease in mice. (22S,23S)-22,23-dihydroxystigmast-4-en-3-one (1) and (22S,23S)-22,23-dihydroxystigmasta-1,4-dien-3-one (2) exhibited anti-HSV-1 activity in vitro and ameliorated the signs of murine herpetic stromal keratitis (HSK), although none of the compounds showed antiviral activity in vivo. We discuss that the improvement of HSK could be due to an immunomodulatory effect of both compounds. © 2008 Elsevier Ltd. All rights reserved.